Uncovering the Dark Side of Ponzi Schemes Through Money Game - Haryadi, Bambang; Wahyudi, Imam; Hayati, Nur (Jurnal Ilmiah Akuntansi dan Bisnis, 2022)
Ponzi schemes with new looks and faces can divert people's views against the suspicions of investment organizers under the guise of Ponzi schemes. The purpose of this study is to reveal the dark side of the practice of Ponzi schemes through money games from the user's perspective. This study uses a qualitative method with a phenomenological approach, the selection of this method is used to achieve the research objectives. Collecting data using observation, interviews, and documentation. The results show, HIPO implementing a Ponzi scheme under the guise of a money game, this can be seen in the work system used by recruiting people and raising funds through offering investment packages as a trap as well as containing elements of gambling. Symptoms of the end of the HIPO as a fraudulent investment are shown through changes to the system and policies by the founders so that members cannot withdraw funds. Keywords : ponzi scheme, money game, dark side